A probabilistic account of the concept of cross-transfer and inferential interactions for trace materials. (30th December 2020) - Taroni, Franco; Juchli, Patrick; Aitken, Colin
Abstract: The analysis of inferential interactions plays an important role in the description of the line of reasoning for a forensic evaluator in a case involving the cross-transfer of evidence. It is possible the two items of evidence may mean more to an evaluator when considered jointly than they do if considered separately. An approach to the evaluation of evidence, with particular attention to the factors that need to be considered, is described for a case involving the cross-transfer of evidence. A formula is given which may be used to define the possible interactions between the evidence transferred in each direction and hence ease the interpretation of such evidence. Numerical examples are given from a classical fibre evidence scenario.